2019
DOI: 10.1519/ssc.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches on Warming up for Sports Performance: A Critical Review

Abstract: WARM-UP PROCEDURES HAVE BECOME RELEVANT FOR COACHES, RESEARCHERS, AND SPORTS PROFESSIONALS IN RECENT YEARS. SEVERAL STUDIES HAVE BEEN CONDUCTED TO VERIFY THE EFFECTS OF DIFFERENT PREACTIVITIES, REGARDING DIFFERING VOLUME, INTENSITY, REST, AND SPECIFICITY, AND THE WARM-UP IS NOW WIDELY ACCEPTED AS AN ESSENTIAL PRACTICE TO IMPROVE PERFORMANCE. RESEARCH IS NOW FOCUSING ON THE EFFECTS OF STATIC AND DYNAMIC STRETCHES, POSTACTIVATION POTENTIATION PHENOMENON, AND OPTIMIZATION OF WAITING PERIODS WITH PASSIVE WARM-UP A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 74 publications
1
47
0
4
Order By: Relevance
“…However, the optimal warm-up method has not been ascertained yet. SS prior to exercise is a common practice to reduce muscle stiffness and increase ROM, but, recently, numerous studies have reported that SS may negatively affect sports performance as a result of changed joint instability or altered optimal intramuscular viscoelastic properties [5,6]. Alternatively, FR has become one of the most popular self-myofascial release (SMR) tools [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optimal warm-up method has not been ascertained yet. SS prior to exercise is a common practice to reduce muscle stiffness and increase ROM, but, recently, numerous studies have reported that SS may negatively affect sports performance as a result of changed joint instability or altered optimal intramuscular viscoelastic properties [5,6]. Alternatively, FR has become one of the most popular self-myofascial release (SMR) tools [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, FR has become one of the most popular self-myofascial release (SMR) tools [7]. FR for SMR could improve ROM while increasing blood flow and circulation to the soft tissues [5,8]. Individuals use their own body weight to apply pressure to target tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Its essence is "the increase in muscle force and RFD that occurs as a result of previous activation of the muscle, as well as the force and power of evoked high velocity shortening contractions, and the maximum velocity attained by evoked shortening contractions under load" (Lorenz, 2011, p. 235). Although the issue remains controversial, previous studies reported a possible ergogenic effect of PAP on acute performance and chronic conditioning strategy, i.e., the so called complex training (Docherty and Hodgson, 2007;Tillin and Bishop, 2009;Wilson et al, 2013;Helena et al, 2019). Most studies were conducted on pairs of lower body activities like squats and vertical jumps, squats and sprints, loaded sprints and unloaded sprints etc.…”
Section: Discussionmentioning
confidence: 99%
“…When a specific warm-up was performed at loads close to the maximum (90% of maximal dynamic [1RM] load), the results demonstrated that the ability to produce maximal dynamic strength could be positively affected [7]. It seems that there is a tendency to use high external loads before power exercises, using the underlying mechanisms resulting from postactivation potentiation, but little are known about the intensities before resistance training sessions [12]. In fact, the postactivation potentiation has been suggested to optimize maximal strength [12,13], but only recently has it been applied to multiple resistance training sets [9].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that there is a tendency to use high external loads before power exercises, using the underlying mechanisms resulting from postactivation potentiation, but little are known about the intensities before resistance training sessions [12]. In fact, the postactivation potentiation has been suggested to optimize maximal strength [12,13], but only recently has it been applied to multiple resistance training sets [9]. It was found that adding three repetitions performed with 90% 1RM load to a specific warm-up of 8 repetitions with 50% 1RM caused an increase of work and number of repetitions performed during three sets until failure with 75% 1RM in bench press exercises [9].…”
Section: Introductionmentioning
confidence: 99%